2005
DOI: 10.1373/clinchem.2004.032458
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Fingerprints for Potential Application to Early Diagnosis of Severe Acute Respiratory Syndrome

Abstract: Background: Definitive early-stage diagnosis of severe acute respiratory syndrome (SARS) is important despite the number of laboratory tests that have been developed to complement clinical features and epidemiologic data in case definition. Pathologic changes in response to viral infection might be reflected in proteomic patterns in sera of SARS patients. Methods: We developed a mass spectrometric decision tree classification algorithm using surface-enhanced la-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…Previous work has illustrated that AEDs are lifesaving, cost-effective, and easy to use by trained and untrained people. 9,[23][24][25][26]27,28 But, a nearby AED that cannot be located quickly might as well not be there at all. AED registration requirements vary by region, however, and a specific agency is not tasked with tracking and maintaining AED locations and use.…”
Section: Number Of Zipcodesmentioning
confidence: 99%
“…Previous work has illustrated that AEDs are lifesaving, cost-effective, and easy to use by trained and untrained people. 9,[23][24][25][26]27,28 But, a nearby AED that cannot be located quickly might as well not be there at all. AED registration requirements vary by region, however, and a specific agency is not tasked with tracking and maintaining AED locations and use.…”
Section: Number Of Zipcodesmentioning
confidence: 99%
“…A related technology, surface-enhanced laser desorption/ ionization time-of-flight mass spectrometry (SELDI-TOF), combined with computational methodologies, has also been used to determine protein profiles (Solassol et al, 2006). Numerous studies have already shown that this methodology can be used to uncover proteomic expression patterns linked with cancer, and some expression patterns have shown high promises in the detection of early-stage cancers (Petricoin and Liotta, 2004;Kang et al, 2005;Kozak et al, 2005;Jacot et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…hydrophobic or hydrophilic mass spectrometer targets) to bind groups of proteins from biological samples and generate distinct mass spectra containing hundreds of peaks (4,5). These so-called proteomic patterns entered mainstream proteomics with the publication of a Lancet study in 2002 (6), which was quickly followed by a significant number of research studies (7)(8)(9)(10)(11)) and reviews (12)(13)(14)(15) describing proteomic patterns capable of discriminating between disease (e.g. ovarian cancer, prostate cancer, etc.)…”
mentioning
confidence: 99%